(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Volterra Integral Equations has wide range of the applications in physics and engineering problems.Spline function can be integrated and differentiated due to being piece wise polynomials and can easily store and implemented on digital computers, nonpolynomial spline function apiece wise is a blend of trigonometric, as well as ,polynomial basis function ,which form a complete extended Chebyshev space.Matlab is a high-level software package with many built in functions that make the learning of numerical methods much easier and interesting.The aims of this paper is to focus and use the sixth order nonpolynomial spline functions to solve linear Voltera integral equations with Weakly Singular Kernel. We followed the applied numerical method using Matlab .Numerical examples are presented to illustrate the applications of this method and to compare the computed results with other numerical methods for exact solutions.